2012
DOI: 10.1111/j.1468-2494.2012.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of the surface energy of human fingernail plates

Abstract: SYNOPSISThe surface energy of the human nail plate is expected to influence the adhesion of microorganisms (and subsequent colonisation and infections) as well as that of medicines (and subsequent drug permeation) and of cosmetics. The aim of the study was therefore to measure the surface energy of nail plates in vivo. The surface energy of healthy human fingernails (untreated, hydrated and abraded) and of hoof membranes (often used as a model for the nailplate) was estimated from contact angle measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It was not practical to use human nailplates for these tests due to their small size and scarcity, and therefore models -high density polyethylene (HDPE) and glass e were used. HDPE was used as its surface energy (35 mJ/m 2 ) [20] is similar to that of the nail plate (34.1 ± 5.5 mJ/m 2 [21], surface energy being known to influence adhesion [22]. Glass was used as it is a commonly used substrate to test adhesion of paints and lacquers.…”
Section: Introductionmentioning
confidence: 99%
“…It was not practical to use human nailplates for these tests due to their small size and scarcity, and therefore models -high density polyethylene (HDPE) and glass e were used. HDPE was used as its surface energy (35 mJ/m 2 ) [20] is similar to that of the nail plate (34.1 ± 5.5 mJ/m 2 [21], surface energy being known to influence adhesion [22]. Glass was used as it is a commonly used substrate to test adhesion of paints and lacquers.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo ungual adhesion of patches showed that, although the patch did not remain adhered at 100% throughout the 2-week study, the patches did adhere to nail plates for several days, as we had previously predicted (Rizi, Mohammed et al 2018), based on their lower surface energies (30 mJ/m 2 ) compared to that of the human nail plate (34.1 ± 5.5 mJ/m 2 ; (Murdan, Poojary et al 2012), reflecting the need for the same or lower surface energy of the adhesive compared to that of the substrate for good intrinsic adhesion, (Venkatraman and Gale 1998).…”
Section: Anti-fungal Efficacy Of Patches Applied To Nail Platementioning
confidence: 53%
“…c) and the mechanical effect of the tool (nail file or nail drill machine) used to prepare the surface of the nail plate (Fig. e,f) …”
Section: Resultsmentioning
confidence: 99%